Formation Control of Multi-Agent Systems with Region Constraint. (4th December 2019) - Yang, Zhengquan; Zhang, Qing; Chen, Zengqiang
Abstract : In this paper, the formation problem for multi-agent systems with region constraint is studied while few researchers consider this problem. The goal is to control all multi-agents to enter the constraint area while reaching formation. Each agent is constrained by a common convex set. A formation control law is presented based on local information of the neighborhood. It is proved that the positions of all the agents would converge to the set constraint while reaching formation. Finally, two numerical examples are presented to illustrate the validity of the theoretical results.